2004
DOI: 10.1002/jlcr.836
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeling of ginkgolide B with 18F

Abstract: SummaryGinkgolide B, a terpene trilactone constituent of Gingko biloba extracts and an antagonist for the platelet activating factor (PAF) receptor, was radiolabeled with the positron emitter 18 F for visualizing its in vivo behavior using positron emission tomography (PET

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The radiosyntheses of the 18 F-labeled GB, 7-18 FGB, and 3 HGB are described elsewhere [11], [12]. The animal experiments were performed according to the animal protocol approved by the Columbia University Medical Center Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiosyntheses of the 18 F-labeled GB, 7-18 FGB, and 3 HGB are described elsewhere [11], [12]. The animal experiments were performed according to the animal protocol approved by the Columbia University Medical Center Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…However, their in vivo behavior in the living body has not been reported. Visualization of their in vivo dynamic distribution by means of an imaging technique such as positron emission tomography (PET) with an analogue of ginkgolides labeled with a positron emitter such as 11 C or 18 F provides unique information which sheds light on the role of ginkgolides in both physiological and pathological conditions. We report here the in vivo behavior of 18 F-labeled ginkgolide B in the rodent visualized by the PET technique for small animals, microPET.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to search for novel targets for ginkgolides, radiolabeled versions of ginkgolides have been prepared including [ 3 H]- and [ 18 F]-labeled GB. , Although biodistribution studies in rats using [ 3 H]-GB showed that GB ( 2 ) entered the brain, the amounts detected in the brain by positron emission tomography (PET) using [ 18 F]-GB was too low to be unambiguously determined . Instead, the first indication of a direct interaction between ginkgolides and important targets in the brain was discovered, when ginkgolides were shown to be potent and highly selective antagonists of the inhibitory strychnine-sensitive glycine receptor (GlyR). The GlyRs are ligand-gated ion channels found primarily in the spinal cord and brain stem, but also in higher brain regions such as the hippocampus and developing cortex.…”
Section: Introductionmentioning
confidence: 99%